Changes in ecosystem carbon following afforestation of native sand prairie - Paul, Eldor A., author; Stromberger, M. E., author; Morris, S. J., author; Drijber, R., author; Hellerich, J., author; Mellor, N. J., author; Soil Science Society of America, publisher (Colorado State University. Libraries, 2013)
Determining the dynamics of carbon (C) as a function of vegetation and residue inputs is important for predicting changes in ecosystem functions and the global C cycle. Litter and soil samples were analyzed from plantations of eastern red cedar (Juniperous virginiana) and ponderosa pine (Pinus ponderosa) and native prairie at the Nebraska National Forest to evaluate the impact of different types of land management on soil C contents and turnover rates. Total soil C to a depth of 1 m was greatest in the cedar stands. Pine ecosystems stored more C in the tree biomass and litter but lost more native prairie C from the soil. The soil 13C content showed 82% of the original, and prairie C remained under cedars compared with ∼45% under pine. Soil cation contents were greatest overall in cedar soils and lowest in pine. The C content in cedar soils was strongly related to Ca content. Differences in microbial community fatty acid profiles were related to vegetation type, and nutrients explained ∼60% of the variation in profiles. Our research indicates that changes in soil C and nutrient content following conversion from prairie to forest are dependent on tree species planted, characteristics of the plant litter, and cation cycling in the plant–soil system.
Keywords: SOC; C pools; global C cycle